2007
DOI: 10.1002/ceat.200700050
|View full text |Cite
|
Sign up to set email alerts
|

Solid Catalyst with Ionic Liquid Layer (SCILL) – A New Concept to Improve Selectivity Illustrated by Hydrogenation of Cyclooctadiene

Abstract: A new concept of a solid catalyst with ionic liquid layer (SCILL) as a novel method to improve the selectivity of heterogeneous catalysts is presented. The sequential hydrogenation of cyclooctadiene (COD) to cyclooctene (COE) and cyclooctane on a commercial Ni catalyst coated with the ionic liquid [BMIM][n-C 8 H 17 OSO 3 ] was tested as first model system. Compared to the original catalyst, the coating of the internal surface with the ionic liquid (IL) strongly enhances the maximum intrinsic COE yield from 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
252
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(265 citation statements)
references
References 31 publications
8
252
0
5
Order By: Relevance
“…In order to calculate D eff , the equation from Froment and Bischoff (1990) was applied. It is valid if a high micro and macro porosity exists in the catalyst (Kernchen et al, 2007).…”
Section: Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to calculate D eff , the equation from Froment and Bischoff (1990) was applied. It is valid if a high micro and macro porosity exists in the catalyst (Kernchen et al, 2007).…”
Section: Componentmentioning
confidence: 99%
“…Sulfidation was carried out from 100 to 350 • C. For the reduction of the catalyst, 10 % H 2 in N 2 flowed through the system. The commercial catalyst (NiSAT 200, Clariant) consisted of porous cylindrical silica particles (length, l = 6 mm; diameter, d = 6 mm) loaded with approximately 37 wt % nickel (Kernchen et al, 2007). Since the sensor catalyst particle and the particles in the fixed bed were nominally identical, i.e., they were from the same batch, the changing electrical properties of the sensor particle reflect the behavior of the particles in the fixed bed.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytically active species can be, for example, solid metal nanoparticles, homogeneous catalyst (metal complexes) in ionic liquid or, for example, enzymes in ionic liquid [23,59,60]. These kind of catalysts are mentioned with different terms in scientific literature, such as SILCA [59], SCILL (supported catalyst with ionic liquid layer) [61], SCIL (supported catalyst with ionic liquid) [62], or SILPC (supported ionic liquid phase catalyst) [63].…”
Section: Supported Ionic Liquid Catalysismentioning
confidence: 99%
“…[16] Interestingly in many cases product selectivities are achieved due to solubility differences between the intermediate and fully hydrogenated products. [24] For example, in the partial hydrogenation of 1,3-butadiene using Pd(0) nanoparticles in [bmim] [BF 4 ], it was observed that 1,3-butadiene is at least three times as soluble in the ionic liquid as the intermediate butenes, inhibiting further hydrogenation and leading to product selectivity. [25] The high viscosity of ionic liquids can also be a limitation for in hydrogenation reactions as diffusion of reactants through the medium is restricted.…”
Section: Kinetic and Thermodynamic Propertiesmentioning
confidence: 99%